An investigation on the behaviour of Minangkabau timber roof truss / Monaleza Zainuddin - Zainuddin, Monaleza (1992)
An important application of the modulus of elasticity of timber is in structural timber design calculations. It is used as a means of estimating the deflection of flexural members and as a parameter in calculating the buck ling strength of timber members. A study is made on the realistic value of the modulus of elasticity of timber members of a Minangkabau Roof Truss configuration. The ANSYS Programme is used to iterate the values of the Modulus of Elasticity of the timber members. This was done in order to obtain the closest deflection of the Minangkabau roof truss at selected points on the truss. The full scale testing was carried out at the Heavy Structures Laboratory of the KARA Institute of Technology. Discrepancies in the value of Modulus of Elasticity of the timber members obtained from the iteration with that obtained using BS 373:1957 (Methods of Testing of Small Clear Specimens of Timber) are described herein.